PROBE DIAGNOSTICS OF THE HEXAFLUORIDE URANIUM PLASMA - Kunakov, S.K. (Recent Contributions to Physics, 2018)
Experimental probe investigations of hexafluoride uranium plasma of high pressure, created by nuclear fragments are оbtained and analyzed.